Combined synchrotron and nonlinear synchrotron-self-Compton cooling of relativistic electrons - Schlickeiser, R.; Böttcher, M.; Menzler, U. (Astronomy and astrophysics (Berlin), 2010)
The broadband SEDs of blazars exhibit two broad spectral components, which in leptonic emission models are attributed to synchrotron radiation and SSC radiation of relativistic electrons. During high state phases, the high-frequency SSC component often dominates the low-frequency synchrotron component, implying that the inverse Compton SSC losses of electrons are at least equal to or greater than the synchrotron losses of electrons. The linear synchrotron cooling, usually included in radiation models of blazars, then has to be supplemented by the SSC cooling. Here, we present an analytical solution to the kinetic equation of relativistic electrons subject to the combined synchrotron and nonlinear synchrotron self-Compton cooling for monoenergetic injection. We calculate the time-dependent fluxes and time-integrated fluences resulting from monoenergetic electrons cooling via synchrotron and SSC, and suggest this as a model for the broadband SED of Compton-dominated blazars.